PELANGGARAN MEREK TERKENAL DAN PERLINDUNGAN HUKUM BAGI PEMEGANG HAK DALAM PERSPEKTIF PARIS CONVENTION, TRIPS AGREEMENT DAN UU MEREK INDONESIA - Windari, Dayu (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2014)
Legal protection for well-known mark owner is important to study because many well-known mark have been infringed domestically and internationaly causing damage to the well-known mark owner. This research discusses 2 (two) main issues namely the legal protection for well-known mark owner and legal action and sanctions imposed against to the infringer by the Paris Convention, TRIPs Agreement and Indonesia Trademark Law. This research applies normative research method. Meanwhile the approach method use statute approach method and comparative approach method which is compares The Paris Convention, TRIPs Agreement and Indonesia Trademark Law regarding the protection of well-known mark. Analysis technique use qualitative analysis. The study shows, from the perspective of the Paris Convention, TRIPs Agreement and Indonesia Trademark Law, well-known mark owner have legal protection in the form of exclusive rights through registration process to obtain legal certainty. When well-known mark infringement occured, the legal action can be done are litigation and non litigation process. The form of legal sanction are payment of compensation and criminal sanction, determined by each member state but still refer to the provisions of the Paris Convention and TRIPs Agreement. However, Indonesia set up more details about the sanctions that can be imposed for the infringemer in the form of penalties or criminal sanction ranging from 4 (four) to 5(five) years and a fine of Rp. 800.000.000 up to Rp. 1.000.000.000
Keywords: Infringement; Legal Protection; Well-Known Mark Owner